THE CONTENT OF MCP-1 AND MMP-9 IN BLOOD SERUM OF PATIENTS WITH CHRONIC POLYPOID RHINOSINUSITIS - Onischenko, A. I.; Nakonechna, O. A.; Tkachenko, A. S.; Kalashnik, Yu. M. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2017)
The content of MCP-1 and MMP-9 inblood serum of patients with chronic polypoid rhinosinusitis was studied. It was found that this pathology led to a significant increase in MCP-1, which is a marker of fibrosis, in blood serum. The compensatory increase in MMP-9, serving as an antifibrotic factor, is much weaker. Such imbalance between profibrotic MCP-1 and antifibrotic MMP-9 indicates a lack of compensatory adaptation mechanisms of fibrolysis activation and contributes to the development of fibrosis in chronic polypoid rhinosinusitis.Chronic polypoid rhinosinusitis is accompanied by an increase in blood serum MCP-1 levels in patients, which indicates the involvement of this chemokine in the proliferation of connective tissue in this pathology. High levels of the antifibrotic proteolytic enzyme MMP-9 are observed in blood serum of patients with chronic polypoid rhinosinusitis, which can serve as a sign of the activation of compensatory adaptive mechanisms aimed at inhibiting the extracellular matrix proliferation. The pronounced increase in MCP-1 levels against the background of a slight activation of MMP-9 in the blood serum of patients with chronic polypoid rhinosinusitis indicates insufficiency of compensatory mechanisms and activation of fibrosis.